Analysis of the Influence of System Quality, Information Quality, Service Quality on User Satisfaction and Continuance Use Intention in the Malang Mbois Application - Sa'idah, Nilna -; Satyareni, Diema Hernyka; Farhan, Ahmad - (Universitas Bina Sarana Informatika, 2025)
The Malang Mbois application is designed to make it easier for the people of Malang City to access public information and service through one integrated application. Although it received a fairly good rating on the Play Store, some users reported problems, such as bugs, incomplete information, and data inaccuracies. The purpose of this study is to investigate the impact of system quality, information, and service on user satisfaction and long-term use of the Malang Mbois Application. This study employs the Delone and McLean models to assess system, information, and service quality, as well as the Expectation Confirmation Model to assess user satisfaction and intent to continue use. Data were collected from 81 application users using purposive sampling technique and analyzed using Stuctural Equation Modeling (SEM) method based on Partial Least Square (PLS) through SmartPLS software. Based on the results of data analysis that has been carried out using SmartPLS software, 4 hypotheses produce a path-coefficient value> 0.1, t-test value ≥ 1.96, p-value ≤ 0.05. The findings indicated that the quality of the system, the quality of information, and the services significantly affect user satisfaction. Additionally, user satisfaction strongly influences the intention of users to keep using the Malang Mbois application.